„WEITER WISSEN. Mit uns.“ Ein Bericht über die Kampagne der wissenschaftlichen Bibliotheken - Ostrzinski, Ulrike (GMS Medizin – Bibliothek – Information)
Academic libraries play a central role as a driving force for open science and society. They provide researchers, academics and students with access to information and promote media literacy. Academic libraries actively shape global information infrastructures and provide access. Key tasks include promoting open access, supporting research data management, preserving cultural heritage, digital long-term archiving and research and development with regard to digital infrastructures. Nevertheless, the importance of academic libraries is not sufficiently recognised everywhere. In addition, funding is not consistently secured in many places. The campaign ‘WEITER WISSEN. Mit uns.’ (in English: ADVANCING KNOWLEDGE. With us.) aims to make the services visible. Decision-makers, the scientific community and funders should recognise the contribution libraries make to high-quality research, science and study.